Influence of nozzle enabling strategy on spray deposition of crop protection unmanned aerial system - Gu, Wei; Xue, Xinyu; Chen, Chen; Zhou, Qingqing; Zhang, Songchao; Peng, Bin (International Journal of Agricultural and Biological Engineering, 2021)
Proper nozzles arrangement is significant to improve spray deposition of crop protection unmanned aerial system (UAS). Besides fuselage structure, the control strategy is another nozzle location changing method when there are multiple sets of nozzles. A four-rotor crop protection UAS equipped with four centrifugal nozzles was used to conduct a field experiment in the rupturing stage of rice. Two sets of nozzles in the front and rear of the fuselage were enabled independently to investigate spray deposition, including spray coverage and droplet density on the sampling cards. Various nozzle rotating speeds and flight speeds were employed in the experiment to study the influence of nozzle location on the deposition. With different nozzle rotating speeds, the droplet spectrum could be controlled. The results show that the average coverage and average cumulative droplet density are negatively correlated with flight speed. Average droplet density is also negatively correlated with the droplet size. Spray deposition of front nozzles is significantly reduced compared with that of the rear nozzles under the same spray parameters, especially when the droplet size is too large or the flight speed is too fast. The reduction is mainly concentrated in the center area of the spray swath. As a result, the average cumulative droplet density of the front nozzles decreases by 25.96% in total. The average droplet density decreases by 18.54% when the droplet size is smaller than 100 μm, decreases by 25.02% when between 100 μm and 200 μm, and decreases by more than half when larger than 200 μm. This research can provide guidance for the installation of UAS nozzles and spray control strategy design.Keywords: crop protection, unmanned aircraft system, nozzles arrangement, spray coverage, droplet densityDOI: 10.25165/j.ijabe.20211404.5922Citation: Gu W, Xue X Y, Chen C, Zhou Q Q, Zhang S C, Peng B. Influence of nozzle enabling strategy on spray deposition of crop protection unmanned aerial system. Int J Agric & Biol Eng, 2021; 14(4): 53–61.